Organizational commitment in the military: Application of a profile approach - Meyer, John; Kam, C.; Goldenberg, I.; Bremner, N. (2013)
According to the 3-component model of commitment, the individual components of commitment-affective (AC), normative (NC), and continuance (CC)-combine to form profiles, and these profiles have different implications for behavior and wellbeing. We tested these propositions in a military context and also examined conditions (perceived organizational support, organizational justice, job satisfaction, and satisfaction with leadership) that might contribute to the development of commitment profiles. Latent profile analyses of data from 6,501 respondents to the 2010 Canadian Forces Retention Survey revealed 6 distinct profiles. Personnel with profiles reflecting strong AC and NC reported the most favorable work conditions, stay intentions, and wellbeing; uncommitted personnel and those with CC-dominant profiles reported the least favorable conditions, were most active in job search activities, and scored highest on anxiety and depression. The value of taking a profile approach, and the implications of managing work conditions to promote optimal profiles, are discussed.